Development Methods of Teaching Disciplines Orchestric SpecializationsII - Tursinovich, Nosirov Dilmurodjon (European Journal of Life Safety and Stability (2660-9630), 2021)
The article notes that one of the reasons for this state of affairs is the unsatisfactory performance of many music vocational education institutions. The management, teaching staff are not always able to orient themselves in the new socio-cultural conditions, find the vectors of educational work that are necessary today, and properly prepare musical youth for the realities of their future professional activities.